Alternative Splicing in Oncogenic Kinases: From Physiological Functions to Cancer - Druillennec, Sabine; Dorard, Coralie; Eychène, Alain (Journal of Nucleic Acids, 2012)
Among the 518 protein kinases encoded by the human kinome, several of them act as oncoproteins in human cancers. Like other eukaryotic genes, oncogenes encoding protein kinases are frequently subjected to alternative splicing in coding as well as noncoding sequences. In the present paper, we will illustrate how alternative splicing can significantly impact on the physiological functions of oncogenic protein kinases, as demonstrated by mouse genetic model studies. This includes examples of membrane-bound tyrosine kinases receptors (FGFR2, Ret, TrkB, ErbB4, and VEGFR) as well as cytosolic protein kinases (B-Raf). We will further discuss how regular alternative splicing events of these kinases are in some instances implicated in oncogenic processes during tumor progression (FGFR, TrkB, ErbB2, Abl, and AuroraA). Finally, we will present typical examples of aberrant splicing responsible for the deregulation of oncogenic kinases activity in cancers (AuroraB, Jak2, Kit, Met, and Ron).